Gendered Pathways Toward STEM Careers: The Incremental Roles of Work Value Profiles Above Academic Task Values - Guo, Jiesi; Eccles, Jacquelynne Sue; Sortheix, Florencia M.; Salmela-Aro, Katariina (Frontiers in Psychology, 2018)
Drawing on Eccles’ expectancy-value model of achievement-related choices, we examined how work values predict individual and gender differences in sciences, technology, engineering, and math (STEM) participations in early adulthood (ages of 25/27, 6 or 8 years after postsecondary school), controlling for subjective task values attached to academic subjects in late adolescence (11th grade, age 18) . The study examined 1259 Finnish participants using a person-oriented approach. Results showed that: a) we could identify four profile groups based on five core work values (society, family, monetary, career prospects, and working with people); b) work-value profiles predicted young adults actual STEM participation in two fields: math-intensive and life science occupations above and beyond academic task values (e.g., math/science) and background information; c) work-value profiles also differentiate between those who entered support- versus professional-level STEM jobs; and d) gender differences in work value profiles partially explained the differential representation of women across STEM sub-disciplines and the overall underrepresentation of women in STEM fields.